Campagne internationale pour la liberation des prisonniers politiques en Amerique Latine (Union Internationale des Étudiants, 1975)
Red rose cutting breaking through barbed wire Poster advertising campaign for release of political prisoners in Latin America, 10 October-31 December, 1975 PO-1400